The Mechanism of Action of Pterostilbene in Xinjiang Wine Grape Against the Growth of Geotrichum citri-aurantii. Issue 3 (2nd July 2016) - Kong, Qingjun; Ren, Xueyan; Tu, LiDan; Zheng, Xiaodong; Wang, Zhidong; Pan, Yuanjiang
ABSTRACT: Pterostilbene controlled the growth of Geotrichum citri-aurantii effectively through experiments of arthroconidium germination on agar plate, which displayed a strong antifungal activity. Observations using light microscope, scanning electron showed that the morphology and inner structure of the G. citri-aurantii treated with the pterostilbene changed notably. Some of the cells were abnormal or lysed. In order to further clarify the molecular mechanism of action, we examined the binding properties exerted by the pterostilbene on DNA and RNA of G. citri-aurantii fungal cells. Results showed that DNA and RNA of the G. citri-aurantii fungal cells were degraded by the pterostilbene. Moreover, three differentially expressed apoptosis genes of fungi were further examined by semi-quantitative RT-PCR. The results indicated that pterostilbene could cause the expression of up-regulated genes involved in RLM1, RTG1, and RTG3, of which the former two genes were significantly up-regulated.